Behavioral Sciences to Protect Human Capital Investments During and after the COVID-19 Pandemic - World Bank (World Bank, Washington, DC, 2020)
The novel coronavirus (SARS-Cov-2, which causes COVID-19) presents multi-dimensional challenges for countries as the effects of the virus, and the response efforts, intersect with other sectors and development priorities. Impacts have been felt across sectors and globally, and there have beenimmediate impacts on human capital attainment and investment.2 The COVID-19 (coronavirus) response, in both the immediate crisis period and the medium/long term, will demand changes in health and other behaviors at the individual, group, and society levels to help mitigate these impacts and risks. Behavioral science can provide insights into designing effective COVID-19 (coronavirus) responses, as well as how to sustain progress in other important areas when resources are focused primarily on urgent COVID-19 (coronavirus) response and attention is limited. At the heart of addressing the COVID-19 (coronavirus) health crisis, from immediate response, to recovery and action on its impacts, lies large demand on behavior change, whether at the individual, group or society level. While much of the immediate focus so far has been on social and behavior change communications to manage infection rates, there are other areas of human capital development and protection where insights and actions can benefit from behavioral science. This note is intended to introduce a behavioral lens to health and nutrition, education, and social protection efforts to reduce negative impacts on human capital accumulation (mainly health, nutrition and education), and to enhance preparedness, response, and adaptation to COVID-19 (coronavirus).